2018
DOI: 10.3390/buildings8090114
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Panel Lay-Up on the Characteristic Bending and Rolling Shear Strength of CLT

Abstract: The objective of this study was to characterise the behaviour of cross laminated timber (CLT) panels and the influence of the panel lay-up on the failure strength. Three different panel configurations of thickness, 60 mm, 100 mm, and 120 mm, were loaded in the out-of-plane direction. The 60 mm and 120 mm panel configuration comprised three layers of equal thickness, and the intermediate 100 mm thick panel comprised five layers of equal thickness. The mean and characteristic bending and rolling shear strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The influence of shear deformations on the cross-layer has also been examined with three-point bending tests in Mastek et al [8] and in Minghao Li [9]. Recently, experimental tests and numerical models have also been presented in Franzoni et al [10], in which the influence of large and small gaps between lateral boards (lamellas) on mechanical behavior of CLT panels subjected to vertical loads with respect to its mid-plane has been highlighted, while experimental measurements of rolling shear properties on soft and hardwood species were carried out by Zhou et al [11] and O' Ceallaigh et al [5]. An extensive experimental campaign (consisting of 342 tests), aimed to evaluate the rolling shear properties of six timber species, with three different sawing patterns and three different aspect ratios of specimens, has been conducted by Ehahart and Brandner [12].…”
Section: Rolling Shear Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of shear deformations on the cross-layer has also been examined with three-point bending tests in Mastek et al [8] and in Minghao Li [9]. Recently, experimental tests and numerical models have also been presented in Franzoni et al [10], in which the influence of large and small gaps between lateral boards (lamellas) on mechanical behavior of CLT panels subjected to vertical loads with respect to its mid-plane has been highlighted, while experimental measurements of rolling shear properties on soft and hardwood species were carried out by Zhou et al [11] and O' Ceallaigh et al [5]. An extensive experimental campaign (consisting of 342 tests), aimed to evaluate the rolling shear properties of six timber species, with three different sawing patterns and three different aspect ratios of specimens, has been conducted by Ehahart and Brandner [12].…”
Section: Rolling Shear Phenomenonmentioning
confidence: 99%
“…As far as the rolling strength is concerned, experimental tests carried out on large scale CLT panels made with three or five layers established a reduced range of characteristic value, from 1.0-2.0 MPa for European spruces, independently from the timber strength class. This topic is beyond the scope of the present paper because the effect of the rolling shear on the deformative flexural behavior of CLT panels is mainly investigated here, whereby additional information can be found in the reference literature works [5,12,14,16].…”
Section: Rolling Shear Phenomenonmentioning
confidence: 99%
“…Results based on 28 FEG specimens. 2 Results based on 3 FEG specimen and/or 3 SEG specimen. 3 Results based on 9 FEG specimen and/or 9 SEG specimen.…”
Section: Single-layer Testsmentioning
confidence: 99%
“…Several studies have investigated parameters that affect the rolling shear strength of CLT panels. O'Ceallaigh et al (2018) [2] tested the bending and shear strength of 3-and 5-layer CLT with different panel thicknesses. The study found that both, bending and rolling shear strength decreases with increasing panel thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of mass timber in the form of cross-laminated timber (CLT) over the past 20 years, however, has necessitated a closer look at strength properties in a plane perpendicular to the grain axis. In particular, for CLT cross laminations, so-called rolling shear [ 3 , 4 , 5 ] is among the dominant failure modes for certain CLT layups. Hence, the motivation for the work described in this paper is to better understand strength and fracture in the plane perpendicular to the grain axis of the wood.…”
Section: Introductionmentioning
confidence: 99%